Outcomes Based Education Curriculum Development in Art Carving Training - Putri, Analita Hanata; Haryono, Haryono; Florentinus, Totok Sumaryanto (Innovative Journal of Curriculum and Educational Technology, 2021)
The Outcomes Based Education (OBE) curriculum is a concept of curriculum that emphasizes the sustainability of the learning process in an innovative, interactive, and effective way. The purpose of this research is to develop carving training curriculum based on the outcomes based education. This research used research and development (R&D) methods and followed the flow of research procedures, start with preliminary study stage development stages, and evaluation stages. The data sources in this research are carving training instructors and carved art trainees. Data collection in preliminary studies done with several instruments, such as observation, interview, and documentation studies. The expert validation in this study were done by curriculum experts and carving assessors. The results of this research stated that the carving curriculum applied in outcome-based education training activities is effective in accordance with the needs of the participants, so that it can be used as a guide for carving training organizers in conducting coaching and training of professional carvers. So, based on the result above, the development of the art curriculum of outcomes based education has implications for strengthening and developing the competencies of carvers especially in work and entrepreneurship, through methods or strategies, relevant media, and proper evaluation systems.